Study on pyrolysis behaviors of L-tyrosine-based phthalonitrile resin. (June 2020) - Zhou, Tao; Xiao, Hang; Peng, Weifeng; Liang, Bo; Liu, Yao; Lv, Jiangbo; Hu, Jianghuai; Zeng, Ke; Yang, Gang
Abstract: The pyrolysis behaviors of l -tyrosine-based phthalonitrile(TPN) resin were investigated by thermogravimetric-Fourier transform infrared spectrometry-mass spectrometry (TG-FTIR-MS) and Pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). The small molecules produced during pyrolysis process of TPN resin were tracked in real time by TG-FTIR-MS. The larger molecules ( m / z  > 40) from fast pyrolysis at 900 °C of the TPN resin using Py-GC/MS were identified. From TG-FTIR-MS and Py-GC/MS results, the production pathways of pyrolysis products such as CO2, CO, NH3, benzonitrile and phenol were analyzed. The possible pyrolysis mechanism of TPN resin under non-oxidizing gaseous environment was proposed. The results of this study provide the useful information for designing the molecular structure of l -tyrosine-based polymers which possessing high thermal stability. Highlights: The pyrolysis behavior of l -tyrosine phthalonitrile resin was studied by TG-FTIR-MS and Py-GC/MS. The process of the thermal degradation was devided into three stages from TG. The main thermal decomposition products were determined.